(untitled) (Journal of Philosophy Culture and Political Science, 2020)
The main purpose of the article is presented an in-depth and comprehensive study vast steppe sacred places’ in the Kazakhs’ habitats, to prove that we do not just have a vast territory, but also our land is rich in spiritual historical heritageю In this case the task of modern scholars show the world Kazakhs’ spiritual heritage, to communicate and familiarize people with the sacred places of Kazakhstan. The article justified by special attention to the fact that the sacred and holy places of Kazakhstan have not only religious significance, but also are important in terms of national and state identities formation, as a factor contributing to the further development of culture, customs and traditions of the people. The territory of Kazakhstan is rich in sacred and holy places. This can be considered as a way to strengthen ethnic and national identities, as well at making Kazakhstan recognizable globally. Currently, historians, researchers, religious scholars are engaged in compiling a single list of sacred places in the territory of modern Kazakhstan, classifying them into international, republican and local levels. In this situation, the most important thing is conducting in-depth research and collecting materials. Still unresolved issues with the criterion for identifying the degree of sacredness of certain objects. Within the framework of this issue, the categorical series has been insufficiently studied, in particular, such terms as «sacred», «holy», as the methodological basis for the study on this range of issues. Given the relevance of this issue, the authors tried to consider some aspects. Key words: sacred places, spiritual modernization, national identity, continuity of sacred places.